Penerapan model think talk write (ttw) guna meningkatkan keterampilan representasi soal cerita materi bangun datar peserta didik kelas ivc sekolah dasar - Nur Hanifah; Siti Wahyuningsih; Siti Kamsiyati (Didaktika Dwija Indria, 2019)
The purpose of this research is improve representation skills in the stories matter by applying Think Talk Write (TTW) learning model. The subjects were 25 a taken from all the students in IVC class at SD Ta’mirul Islam Surakarta in the 2018/ 2019. This research is classroom reseach with three cycles. Data collection technique are using test, observation and documentation with data analysis of technique triangulation, source triangulation and content validity. The initial condition of representation skills in IVC class students showed 4% classically. The first cycle began with the first learning resulting in percentage of 21.7% in classical the second learning was 40.90 % in classical. The study continued with the second cycle with the percentage of achievement at the first learning amounting 61.90 % in classical, the second was 77.30%. The sudy continued with third cycles with the first learning persentage of 84.00% and the second was 87.00%.